Hak Moral Kekayaan Intelektual: Telaah Etis Penggunaan Karya Cipta Tanpa Izin di Platform Media Sosial - Darwance, Darwance; Supriyanto, Agustinus (PROGRESIF: Jurnal Hukum, 2024)
Basically, humans are always required to use their minds to think about God's creation, because thinking is an activity that humans cannot avoid in their lives. From this thought process, Intellectual Property Rights (IPR) were born which differ from one human to another because each human has different intellectual abilities. On the other hand, violations of IPR, such as unauthorized use or purchase of pirated works, continue to occur. This violation is not only against norms, but also morals and ethics. This research examines the relationship between ownership of IPR and violations of IPR from a moral and ethical perspective. From the results of the study conducted, the results show that violations of IPR are not only violations of norms, but also ethics. One form of ethical violation is the use of other people's work without mentioning the name of the rights holder, for example the creator. Ethically, this is contrary to moral values.